FEASIBILITY STUDY OF THE LOCATION AND CULTIVATION OF TILAPIA AT KADEN FARM, BABAKAN PANJANG VILLAGE, SUKABUMI DISTRICT - Amalia Putri Firdausi; Muhammad Sahlan Firjatullah; Reta Sagita; Riem Rahayu Rahman; Rahmah Mulanti; Bintan Naktavia; Muhammad Aqshol Dafa Ramadhan; Zacky Naoval Nainggolan; Jemmy Erwanda Maulana; M. Isya Rais A.; Fika Ismaladewi; Aulia Herlita; Hikmal Yumilzam; Nadira Khalisha; ⁠Maulana Ishaq; ⁠Sofyan Alhaq; Abrisam Hadi Bintoro; Achmad Zidan Akmal Maulana; Risma Arafah Tunisa; Wildan Nurussalam (Universitas Mataram, 2024)
Selecting an optimal aquacultural site can enhance feed efficiency and diminish production costs. Tilapia cultivated in an optimal environment will more readily digest feed and utilize nutrients. This research was conducted through field observations, including soil sampling, water quality measurements, and production performance assessments. The results of the soil texture analysis performed on the two ponds at Kaden Farm indicated that the proportion of sand ranged between 17–18%, dust 42–43%, and clay 40–42%. The water quality was 'slightly suitable,' with a suitability index of 66.67% for Pond 1 and 71.01% for Pond 2. The production performance of the tilapia, as indicated by the survival rate reached 70%, the relative growth rate was 0.017 g/day, and the specific growth rate reached 14.62%. Cultivating tilapia at Kaden Farm in terms of pond media in the form of soil is feasible for cultivation. The results indicate that water quality is slightly below the expected standards. The tilapia production at Kaden Farm is feasible based on the observed survival, relative growth rate, and specific growth rate.